2020
DOI: 10.1136/jitc-2019-000489
|View full text |Cite
|
Sign up to set email alerts
|

Melanoma-specific bcl-2 promotes a protumoral M2-like phenotype by tumor-associated macrophages

Abstract: BackgroundA bidirectional crosstalk between tumor cells and the surrounding microenvironment contributes to tumor progression and response to therapy. Our previous studies have demonstrated that bcl-2 affects melanoma progression and regulates the tumor microenvironment. The aim of this study was to evaluate whether bcl-2 expression in melanoma cells could influence tumor-promoting functions of tumor-associated macrophages, a major constituent of the tumor microenvironment that affects anticancer immunity favo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 51 publications
0
28
0
Order By: Relevance
“…Increased levels of Bcl-2 expression have been also associated with resistance to different drugs including 5-fluorouracil in gastric cancer [23] cisplatin in ovarian cancer [24] and doxorubicin in osteosarcoma and chondrosarcoma [25,26]. In the last years, our group demonstrated that, in addition to its important role in the regulation of apoptosis and chemoresistance [27], Bcl-2 modulates in vitro and in vivo tumor migration, invasion, autophagy and angiogenesis [28][29][30][31][32][33], promotes a cancer stem-like cell phenotype [34], regulates the expression of microRNA and the activity of several transcription factors and their specific target genes [35][36][37], controls an interleukin-1β-driven axis of macrophage diversion that establishes tumor microenvironmental conditions favoring melanoma development [38] and is involved in mitochondrial mRNA homeostasis [39]. We and other authors demonstrated several non-canonical functions of Bcl-2, as well as other anti-apoptotic proteins, in an apoptosis-independent manner [40].…”
Section: Bcl-2mentioning
confidence: 99%
“…Increased levels of Bcl-2 expression have been also associated with resistance to different drugs including 5-fluorouracil in gastric cancer [23] cisplatin in ovarian cancer [24] and doxorubicin in osteosarcoma and chondrosarcoma [25,26]. In the last years, our group demonstrated that, in addition to its important role in the regulation of apoptosis and chemoresistance [27], Bcl-2 modulates in vitro and in vivo tumor migration, invasion, autophagy and angiogenesis [28][29][30][31][32][33], promotes a cancer stem-like cell phenotype [34], regulates the expression of microRNA and the activity of several transcription factors and their specific target genes [35][36][37], controls an interleukin-1β-driven axis of macrophage diversion that establishes tumor microenvironmental conditions favoring melanoma development [38] and is involved in mitochondrial mRNA homeostasis [39]. We and other authors demonstrated several non-canonical functions of Bcl-2, as well as other anti-apoptotic proteins, in an apoptosis-independent manner [40].…”
Section: Bcl-2mentioning
confidence: 99%
“…After its initial suc9cess in the treatment of metastatic melanoma, the clinical application of checkpoint inhibitors has rapidly spread to the majority of cancer cases with varying degrees of success. Among several cancer types, melanoma remains one of the most positively impacted by the use of these molecules, most likely because of its high mutational rate as well as to the frequent generation of an inflammatory microenvironment which together help establish appropriate conditions for the immune-system to respond ( 90 , 91 ). In stage IV melanoma, five year overall survival rates obtained with the combination of ipilimumab and nivolumab are currently up to 52% ( 92 ).…”
Section: Final Considerationsmentioning
confidence: 99%
“…In in vitro three-dimensional models, IL-10 has been shown to be released also by melanoma cells leading to the induction of an M2-like phenotype in myeloid cells [ 15 ]. Furthermore, in melanoma cells, overexpression of bcl-2 correlated with the tumor ability to reprogram macrophage polarization toward M2 through bcl-2-dependent IL-1β production [ 16 ]. Modifications of the TME further increase the heterogeneity of M2-TAMs; even in the same tumor model, different subtypes of M2-TAMs could be distributed in different regions, i.e., M2a-, M2b-, and M2c-TAMs.…”
Section: From Circulating Monocytes To Tumor-associated Macrophagementioning
confidence: 99%